ANALISIS RESPONS STRUKTUR SISTEM RANGKA PEMIKUL MOMEN KHUSUS DENGAN GEMPA DINAMIK RESPONS SPEKTRUM MENGGUNAKAN SAP2000 - Jaya, Purnawi; Defiana, Yanti; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2025)
Indonesia is one of the countries located on the Pacific Ring of Fire, making it highly vulnerable to earthquakes. This condition requires that the design of building structures comply with seismic code provisions to ensure ductile behavior and safety under earthquake loads. One of the structural systems recommended for regions with high seismic design categories is the Special Moment Resisting Frame (SMRF), due to its high ductility capacity and effectiveness in dissipating seismic energy. This study aims to analyze the structural response of a building using the SMRF system under dynamic earthquake loading through the response spectrum method based on SNI 1726:2019. The analysis was carried out using SAP2000 software, with spectral response parameters (Ss, S1, Fa, Fv, SMS, SM1, SDS, and SD1) determined to classify the seismic design category. The building structure was then modeled under response spectrum earthquake loading to evaluate its behavior in terms of displacement, inter-story drift, base shear, and fundamental period. The analysis results indicate that SDS > 0.5 g and SD1 > 0.2 g, placing the building in Seismic Design Category D. The SMRF structural model meets the requirements of SNI 1726:2019, with inter-story drifts remaining below the maximum limit of 2%, while the base shear and fundamental period comply with code provisions. Therefore, the application of the SMRF system is considered feasible and suitable for building structures located in high seismic risk regions.